A technology for online parameter identification of permanent magnet synchronous motor - Ma, XiaoJun; Bi, Chao (CES Transactions on Electrical Machines and Systems, 2020)
Accuracy of the motor parameters is important in realizing high performance control of permanent magnet synchronous motor (PMSM). However, the inductance and resistance of motor winding vary with the change of temperature, rotor position and current frequency. In this paper, a technology based on circuit model is introduced for realizing online identification of the parameter of PMSM. In the proposed method, a set of nonlinear equations containing the parameters to be identified is established. Considering that it is very difficult to obtain the analytical solution of a nonlinear system of equations, Newton iterative method is used for solving the equations. Both the simulation and testing results confirm the effectiveness of the method presented.